The incidence of unexpected critical complications in monochorionic diamniotic twin pregnancies according to the interval period between ultrasonographic evaluations. Issue 2 (10th October 2018) - Kawaguchi, Haruna; Ishii, Keisuke; Muto, Haruka; Yamamoto, Ryo; Hayashi, Shusaku; Mitsuda, Nobuaki
Abstract: Aim: This study aimed to evaluate the incidence of unexpected critical complications (UCC) in monochorionic diamniotic (MCDA) twin pregnancies according to ultrasonographic scan interval. Methods: This retrospective single‐center cohort study, conducted between January 2005 and April 2015, investigated the incidence of UCC in patients with MCDA twin pregnancies undergoing weekly ultrasound (Group A) and those undergoing biweekly ultrasound (Group B). We also examined the incidence of predictable critical complications according to ultrasound interval. Results: Of all 385 cases, the total incidence of UCC was 20 (5.2%), including 14 cases of twin‐twin transfusion syndrome and 6 cases of intrauterine fetal death. The incidence of UCC was 3.9% in Group A and 9.0% in Group B ( P = 0.046). In contrast, the incidence of predictable critical complications was 6.7% in Group A and 9.0% in Group B ( P = 0.440). Conclusion: The incidence of UCC in patients with MCDA twin pregnancies was significantly lower in patients undergoing weekly ultrasound. Our results suggest that weekly ultrasound evaluation for patients with MCDA pregnancy is more effective for early detection of UCC such as intrauterine fetal death and twin‐twin transfusion syndrome ; however, further investigations are needed to determine whether weekly ultrasound evaluation can improve clinical outcomes.